Bioactive Edible Films and Coatings Based in Gums and Starch: Phenolic Enrichment and Foods Application - Pedreiro, Sónia Raquel Jorge (2021)
Edible films and coatings allow preserving fresh and processed food, maintaining quality, preventing microbial contamination and/or oxidation reactions and increasing the shelf life of food products. The structural matrix of edible films and coatings is mainly constituted by proteins, lipids or polysaccharides. However, it is possible to increase the bioactive potential of these polymeric matrices by adding phenolic compounds obtained from plant extracts. Phenolic compounds are known to possess several biological properties such as antioxidant and antimicrobial properties. Incorporating phenolic compounds enriched plant extracts in edible films and coatings contribute to preventing food spoilage/deterioration and the extension of shelf life. This review is focused on edible films and coatings based on gums and starch. Special attention is given to bioactive edible films and coatings incorporating plant extracts enriched in phenolic compounds.